2018
DOI: 10.21873/anticanres.12467
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Perioperative Chemotherapy in Squamous Cell Carcinoma of the Upper and Lower Urinary Tract

Abstract: Abstract. Background Although urothelial carcinoma (UC) represents the majority of bladder tumours, with rates ranging between 90% and 95%, bladder cancer encompasses a wide spectrum of malignancies including squamous cell carcinoma (SCC; 2-5%), adenocarcinoma (0.5-2%), small cell carcinoma (<1%) and other less common histological types (1). In contrast, SCC represents 1-2% of all upper urinary tract (UT) cancers; thus, establishing a standard of care for SCC is difficult and the prognosis remains poor due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition, the prevalence of HV has increased consistently during the years. Indeed, Marco et al (10) (6). Shah et al (13) reported that 44% of HV were not recognized by referring institutions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prevalence of HV has increased consistently during the years. Indeed, Marco et al (10) (6). Shah et al (13) reported that 44% of HV were not recognized by referring institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Mitra et al found that UCSD and UCGD have a significantly more advanced clinical stage upon diagnosis compared with PUC and are associated with poor prognosis (7). For chemotherapy, there are both reports of similar response to PUC and reports showing worse response (3,8,9). Although many studies on the prognosis of muscleinvasive BC with VH have been conducted, only a few have focused on pathological T1 (pT1) cases of invasion of the lamina propria.…”
mentioning
confidence: 99%